2018
DOI: 10.1111/faf.12286
|View full text |Cite
|
Sign up to set email alerts
|

The sceptical optimist: challenges and perspectives for the application of environmental DNA in marine fisheries

Abstract: Application of environmental DNA (eDNA) analysis has attracted the attention of researchers, advisors and managers of living marine resources and biodiversity. The apparent simplicity and cost‐effectiveness of eDNA analysis make it highly attractive as species distributions can be revealed from water samples. Further, species‐specific analyses indicate that eDNA concentrations correlate with biomass and abundance, suggesting the possibility for quantitative applications estimating abundance and biomass of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
236
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(241 citation statements)
references
References 129 publications
(324 reference statements)
5
236
0
Order By: Relevance
“…We support current recommendations that advise pilot studies be performed on new systems/organisms before implementing eDNA monitoring (Hansen, Bekkevold, Clausen, & Nielsen, 2018;Harper et al, 2018), and furthermore, we encourage the publication of unsuccessful eDNA studies to better inform the eDNA research community, reduce financial and time losses due to ineffective study designs, and thereby aid the continued success of eDNA applications in future studies. Undoubtedly, eDNA has great potential in the context of cetacean monitoring and management, but as a complimentary additional tool rather than an outright replacement of tried and tested techniques.…”
Section: Con Clus Ionsupporting
confidence: 64%
“…We support current recommendations that advise pilot studies be performed on new systems/organisms before implementing eDNA monitoring (Hansen, Bekkevold, Clausen, & Nielsen, 2018;Harper et al, 2018), and furthermore, we encourage the publication of unsuccessful eDNA studies to better inform the eDNA research community, reduce financial and time losses due to ineffective study designs, and thereby aid the continued success of eDNA applications in future studies. Undoubtedly, eDNA has great potential in the context of cetacean monitoring and management, but as a complimentary additional tool rather than an outright replacement of tried and tested techniques.…”
Section: Con Clus Ionsupporting
confidence: 64%
“…The significant water displacement at our study site (Old & Vennell, ), however, could cause dilution rates to occur that lower DNA concentrations of a particular source rapidly beyond the limit of detection (Thomsen et al, ). Also, it has been posited that coastal regions might be less affected by eDNA transport, due to coastal morphology or retentive properties of seaweed (Hansen et al, ). Further investigation into the differences between coastal and offshore environments is therefore needed.…”
Section: Discussionmentioning
confidence: 99%
“…Community composition is expected to differ between sampling media, as previous eDNA studies have found sediment to show a higher DNA concentration and a longer detectability than surface water (Turner et al, 2015). Since DNA can persist longer when incorporated into the sediment, temporal inference may be challenging (Turner et al, 2015); on the other hand, a higher degradation rate and lower detection lag time in aqueous eDNA samples provide a contemporary snapshot of the biodiversity being assessed (Hansen et al, 2018). Here, we have found a significant difference (p < 0.05) and a higher size effect (R 2 = 0.06-0.08) on MOTU recovery between sediment and water samples ( (Shogren et al, 2017).…”
Section: Community Composition Across Treatmentsmentioning
confidence: 99%